2015
DOI: 10.3390/jcm4081561
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic/Race Diversity and Diabetic Kidney Disease

Abstract: Ethnicity and race are often used interchangeably in the literature. However, the traditional definition of race and ethnicity is related to biological (bone structure and skin, hair, or eye color) and sociological factors (nationality, regional culture, ancestry, and language) respectively. Diabetes mellitus (DM) is a huge global public health problem. As the number of individuals with Type 2 DM grows, the prevalence of diabetic kidney disease (DKD), which is one of the most serious complications, is expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 12 publications
0
5
2
Order By: Relevance
“…Renal effects of dapagliflozin treatment are of particular interest because SGLT2 is expressed almost exclusively in the kidney. Asian patients with T2DM have been noted to be particularly susceptible to kidney disease . Overall, there were no clinically meaningful changes in eGFR in the present analysis.…”
Section: Discussioncontrasting
confidence: 62%
“…Renal effects of dapagliflozin treatment are of particular interest because SGLT2 is expressed almost exclusively in the kidney. Asian patients with T2DM have been noted to be particularly susceptible to kidney disease . Overall, there were no clinically meaningful changes in eGFR in the present analysis.…”
Section: Discussioncontrasting
confidence: 62%
“…A number of studies indicate that the risk of the development and progression of diabetic nephropathy varies among different populations . The incidence of ESRD attributable to both Type 1 diabetes (T1DM) and T2DM is higher among South Asian than white European people .…”
Section: Introductionmentioning
confidence: 99%
“…9 A number of studies indicate that the risk of the development and progression of diabetic nephropathy varies among different populations. 8,10,11 The incidence of ESRD attributable to both Type 1 diabetes (T1DM) and T2DM is higher among South Asian than white European people. 12,13 The literature on diabetic nephropathy in ethnic groups, however, is sparse and varied and it is not clear whether progression or higher levels of urine albumin excretion influence similar rates of estimated glomerular filtration rate (eGFR) decline among different ethnic populations, despite similar competing risks, and therefore may impact rates of prevalence of ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a rising body of evidence suggesting that individuals of certain ethnics and racial origins have more susceptibility to develop diabetes and her complications macro and microvascular such renal dysfunction, as described in the present study. Specially, evidence identified that patients with proteinuria and particularly those of ethnicity/race, from south Asia and black people present high risk to renal dysfunction and can be benefited with additional monitoring in a specialized clinic (20) .…”
Section: Discussionmentioning
confidence: 99%